A critical analysis of the taxation of cross-border service fees in South Africa: Motivation for the reinstatement of the withholding tax on service fees - Xulu, Mbali (University of Cape Town, 2019)
South Africa has seen a growth in cross-border services in the last decade. This comes as no surprise since, as early as 2010, the global service sector accounted for approximately 70% of the world’s Gross Domestic Product. Given the magnitude of the service sector, it is imperative that South Africa implements laws that seek to tax service fees in an efficient, effective and equitable manner. South Africa’s Minister of Finance and the Davis Tax Committee are amongst the key government stakeholders who have expressed concern regarding the threat that South Africa faces to the erosion of its tax base as a result of outward cross-border service fees. The tax base erosion typically occurs when a non-resident derives a service fee from South Africa which is not taxed in South Africa, whilst the resident payor is allowed to claim a deduction. As a means of addressing the above threat, South Africa introduced the withholding tax on service fees regime. This withholding tax was intended to apply on service fees derived by a non-resident from a source in South Africa. However, as the application of this withholding tax was subject to the application of the relevant double tax treaties, South Africa’s right to impose this withholding tax was in most cases limited. The withholding tax on service fees regime was therefore repealed. With the withdrawal of the withholding tax on service fees, South Africa can only tax service fees to the extent that they are derived by a non-resident from a source in South Africa and attributable to the non-resident’s permanent establishment situated in South Africa. In terms of the Organisation for Economic Co-operation and Development Model Tax Convention ('OECD MTC’), a permanent establishment is defined as essentially comprising of a fixed place of business whilst, under the United Nations Model Tax Convention9 ('UN MTC’), this definition is extended to include the provision of services by a non-resident who is at least present in South Africa for more than 183 days in any 12-month period rendering services in connection with the same or connected project. Globalisation and electronic commerce has made the remote provision of services possible. It has therefore become relatively easy for a non-resident business to render services in South Africa without the presence of a fixed place of business or without being present in South Africa for substantial periods and thereby avoid being subjected to income tax in South Africa on the service income derived. In light of the above, this dissertation argues that the permanent establishment threshold is no longer appropriate for the taxation of services. Specifically, it is contended that the permanent establishment threshold is excessively high and as a result contributes towards the erosion of the source state’s tax base. Various options for addressing this concern are then explored and a recommendation is made that South Africa should negotiate for the inclusion of the technical fee article in its double tax treaties and re-instate the withholding tax on service fees regime.